Intra-articular morphine enhances analgesic efficacy of ropivacaine for knee arthroscopy in ambulatory patients. - Lykoudi, Irini; Kottis, George; Nikolaou, Vassilios S; Setaki, Pandora; Fassoulaki, Argyro; Efstathopoulos, Nicolas (Orthopedics, 2011)
The aim of this double-blind, randomized control trial was to compare the effectiveness of intra-articular ropivacaine alone or with morphine or ketoprofen for controlling pain after arthroscopic knee surgery. One hundred fifty-six patients scheduled for elective knee arthroscopy were recruited. All patients received general anesthesia and were randomly assigned to 4 groups to receive intra-articular ropivacaine 40 mg (group R), ropivacaine 24 mg plus morphine 8 mg (group R+M), ropivacaine 36 mg plus ketoprofen 100 mg (group R+K), or normal saline (group N/S). Pain, sedation, orientation, nausea, vomiting, and urine retention were recorded at 0, 1, 2, 4, 8, 12, and 24 hours postoperatively. Pain was evaluated by a 10-cm visual analog scale (VAS). When the pain was >2, a suppository of 400 mg paracetamol plus 10 mg codeine plus 50 mg caffeine was given. Results showed that at 4 hours postoperatively, pain differed significantly among the 4 groups (P<.001), with less pain recorded in the R+M group. Similarly, the number of suppositories administered postoperatively to the R+M group was significantly less (P<.001) vs the other groups. Patients who received ropivacaine and morphine or normal saline had a higher incidence of nausea and vomiting vs the other groups (P=.001 and P=.036, respectively). The combination of intra-articular ropivacaine and morphine is associated with less pain after knee arthroscopy during early recovery but with a higher incidence of nausea and vomiting. However, the addition of ketoprofen to ropivacaine provides relatively satisfactory pain relief, but with fewer side effects compared to morphine.
Keywords: Adult; Ambulatory Care; Amides; Analgesics, Opioid; Anesthetics, Local; Arthralgia; Arthroscopy; Double-Blind Method; Drug Synergism; Drug Therapy, Combination; Female; Humans; Knee Joint; Male; Morphine; Pain, Postoperative; Ropivacaine; Treatment Outcome